Questionnaire validation practice: a protocol for a systematic descriptive literature review of health literacy assessments - Melanie Hawkins; Gerald R Elsworth; Richard H Osborne (BMJ Open)
Introduction Contemporary validity testing theory holds that validity lies in the extent to which a proposed interpretation and use of test scores is justified, the evidence for which is dependent on both quantitative and qualitative research methods. Despite this, we hypothesise that development and validation studies for assessments in the field of health primarily report a limited range of statistical properties, and that a systematic theoretical framework for validity testing is rarely applied. Using health literacy assessments as an exemplar, this paper outlines a protocol for a systematic descriptive literature review about types of validity evidence being reported and if the evidence is reported within a theoretical framework.Methods and analysis A systematic descriptive literature review of qualitative and quantitative research will be used to investigate the scope of validation practice in the rapidly growing field of health literacy assessment. This review method employs a frequency analysis to reveal potentially interpretable patterns of phenomena in a research area; in this study, patterns in types of validity evidence reported, as assessed against the criteria of the 2014 Standards for Educational and Psychological Testing, and in the number of studies using a theoretical validity testing framework. The search process will be consistent with the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Outcomes of the review will describe patterns in reported validity evidence, methods used to generate the evidence and theoretical frameworks underpinning validation practice and claims. This review will inform a theoretical basis for future development and validity testing of health assessments in general.Ethics and dissemination Ethics approval is not required for this systematic review because only published research will be examined. Dissemination of the review findings will be through publication in a peer-reviewed journal, at conference presentations and in the lead author’s doctoral thesis.